Comparative Analysis between Real Cost and INA-CBG’s claims of Service Costs in Chronic Kidney Disease Patients with Hemodialysis - Nadhira, Riqqah; Saputra, Irwan; Usman, Said; Bakhtiar, Bakhtiar; Nurjannah, Nurjannah (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study was an observational analytic study conducted in the Hemodialysis unit of Zainal Abidin Hospital (RSUDZA), Banda Aceh, Indonesia. Data collection was carried out by taking secondary data from CKD patient visits in January-December 2019. The study population was all CKD patients in the registry of 2019 in the hospital, with a total of 406 patients enrolled. The highest unit cost of care based on real costs was the cost of surgical procedures, and the cost difference between INA-CBG’s and hospital tariffs in the treatment of patients with CKD is significantly different (p-value = 0.014, with gap difference of IDR 2,146,086). It is suggested an urgent evaluation and scrutinization for the management of CKD patients with hemodialysis to prevent the different treatment costs in the service